Energy sources in the supplementation of beef cattle grazing Brachiaria brizantha cv. Xaraés - José Neto, Antônio [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In the first experiment, one hundred and four (initial BW = 284 ± 38 kg) and sixty (initial BW = 424 ± 34 kg) Nellore bulls were used to evaluate the performance and final carcass characteristics of Nellore bulls during two phases: growing and finishing phase, respectively. The diets used consisted in Brachiaria brizantha cv. Xaraés pasture supplemented with two levels of starch, with or without a source of oil. The supplements were corn associated or not with ground soybean (GS) and soybean hulls (SH) associated or not with ground soybean. In relation to animal performance during growing phase, there were no interaction (P = 0.14) between starch level and oil for final BW, ADG, and CrG. However, the addition of oil decreased final BW (P = 0.01), ADG (P < 0.01), total gain (P < 0.01) and CrG (P = 0.01). On the other hand, during finishing phase, there were no interaction (P = 0.11) between starch level and oil for, final BW, ADG, HCW, dressing, CrG, fat depth, and LM area. In contrast, animals supplemented with oil increased final BW (P = 0.01), ADG (P = 0.02), total gain (P = 0.01), HCW (P < 0.01), CrG (P = 0.01), and fat depth (P = 0.04). Furthermore, there was effect of time during growing and finishing phase on values of ADG (P < 0.01) of Nellore bulls. Soybean hulls have a similar energy value to corn when used in supplements to beef cattle on tropical pasture during growing and finish phase. The use of oil supplementation may be effective to reduce enteric CH4 emissions of Nellore bulls fed Brachiaria brizantha cv. Xaraés during the growing and finishing phase, and in addition, may improve performance and final carcass traits of Nellore bulls, only during the finish phase. In another experiment, aimed to evaluate the combined effects of high- or low-starch supplements and oil on intake, digestibility, performance, and methane (CH4) emissions of growing (n = 44, initial BW = 250.69 ± 27 kg) and finishing (n = 44, initial BW = 414 ± 12 kg) Nellore bulls fed tropical pasture of Brachiaria brizantha cv. Xaraés during the rainy and dry season, respectively. Eight animals were slaughtered at a commercial beef plant and served as the reference group at the beginning of each experiment. The other thirty-six animals were distributed in a completely randomized design (three animals per paddock and three paddocks per treatment). The experimental period lasted 133 d, divided into an adaptation period of 21 d and four periods of 28 d each. The supplements were: corn combined with GS; corn without GS; SH combined with GS; and SH without GS. Crude glycerin was used in all supplements to replace (28% of DM) corn or SH. In relation to growing phase, there were no interactions between starch level and oil supplementation on intake of DM (P = 0.67), NDF (P = 0.50), and EE (P = 0.47); on digestibility of DM (P = 0.18) and NDF (P = 0.42); on final BW (P = 0.94), ADG (P = 0.40), FE (P = 0.37); and on CH4 emissions when expressed in g/d (P = 0.77), kg/yr (P = 0.77), g/kg DMI (P = 0.53). However, independently of starch level utilized, the animals supplemented with oil increased intake of EE (P < 0.01); decreased the digestibility of OM (P = 0.04) and NDF (P = 0.03); and decreased enteric CH4 emission when corrected for intake of GE (P = 0.04) and EE (P < 0.01). In finishing phase, there were no interactions between starch level and oil supplementation on intake of DM (P = 0.90), NDF (P = 0.65), and EE (P = 0.56); on digestibility of DM (P = 0.12) and NDF (P = 0.12); on final BW (P = 0.37), ADG (P = 0.41), FE (P = 0.47), HCW (P = 0.83), dressing (P = 0.41), carcass gain (P = 0.98), fat depth (P = 0.36) and LM area (P = 0.91); and on CH4 emissions when expressed in g/d (P = 0.78), kg/yr (P = 0.78), g/kg DMI (P = 0.81), g/kg ADG (P = 0.48), and g/kg of carcass gain (P = 0.85). However, independently of starch level utilized, the animals supplemented with oil decreased the digestibility of NDF (P = 0.03) and increased EE digestibility (P < 0.01); increased the fat depth (P = 0.01); and decreased enteric CH4 emission expressed in g/d (P = 0.04) and kg/yr (P = 0.04), and when was corrected to GE (P = 0.02) and EE (P < 0.01) intake, and ADG (P = 0.02) for animals fed high- or low-starch supplement. In growing or finishing phase, soybean hulls have the similar estimated feeding value to that of corn, and the use of oil supplementation may be effective to reduce enteric methane emission of Nellore bulls grazing tropical pasture. Regarding the study of cannulated animals, the objective was evaluate the effect of oil supplementation combined with high- or low-starch on intake, nutrient digestibility, rumen fermentation parameters, and rumen microbial profile of young Nellore steers grazing Brachiaria brizantha cv. Xaraés during two phases: growing and finishing. In the growing phase, eight ruminal cannulated Nellore steers (424.8 kg ± 35.5) at 20 mo of age were used in a replicate 4 × 4 Latin square with a 2 × 2 factorial arrangement of treatments (high or low starch, with or without a source of oil) and an experimental period of 21 d. The supplements were corn combined with GS; corn without GS; SH combined with GS; and SH without GS. Animals were supplemented at the rate of 500 g/100kg BW. There were no interactions between starch level and oil supplementation on DM and nutrients intake (P > 0.01). The addition of oil decreased the intake of DM (P = 0.01), forage DM (P < 0.01), OM (P = 0.01), CP (P = 0.02), NDF (P < 0.01), and GE (P = 0.01), independently of starch level used. Animals fed with low-starch and without oil had greater digestibility of DM (P < 0.01), OM (P < 0.01), CP (P < 0.01), NDF (P = 0.01), and GE (P = 0.01) than animals fed with other supplements. The addition of oil in the supplements decreased the pH (P = 0.02) and NH3-N (P = 0.02); and decreased the numbers of Dasytricha (P < 0.01), Isotricha (P < 0.01), and total protozoa (P < 0.01). The percentage of Ruminococcus albus (P = 0.0003), Ruminococcus flavefaciens (P = 0.0002), and Archeas (P < 0.0004) were higher for low-starch without oil diets than for other diets. Additionally, animals supplemented with oil decreased the number of Fibrobacter succinogenes (P = 0.0003), independently of starch level used. Oil supplementation reduce intake, protozoa population, and fibrolytic rumen bacteria. The use of low-starch supplementation without oil may be effective to increase digestibility of DM and nutrient, and Ruminococcus albus, Ruminococcus flavefaciens, and Archeas population in the rumen of growing Nellore steers grazing tropical pasture. In the finishing phase, eight ruminal cannulated Nellore steers (514.5 kg ± 30.1) at 24 mo of age were used in a replicate 4 × 4 Latin square with a 2 × 2 factorial arrangement of treatments (high or low starch, with or without a source of oil) and an experimental period of 21 d. The supplements were corn combined with GS; corn without GS; SH combined with GS; and SH without GS. Animals were supplemented at the rate of 1000 g/100 kg BW. There were no interactions between starch-based supplementation level and oil with regard to DM and nutrients intake (P > 0.05). Animals supplemented with low starch and no oil showed greater (10.77%) digestibility of CP (P = 0.01) than those supplemented with high-starch and no oil. Total apparent digestibility of DM (P < 0.01), OM (P < 0.01), NDF (P = 0.03), and GE (P = 0.02) decreased with oil supplementation. There were no interactions between starch × oil for pH, NH3-N, and total VFA (P > 0.05). Animals supplemented with oil showed lower acetate production (P < 0.01) than those supplemented without oil, independent of starch level. The addition of oil in the supplements decreased the population of Dasytricha (P < 0.01), Polyplastron (P < 0.21), and Diploplastron (P = 0.04). Supplementing the animals with low-starch without oil increased the numbers of Ruminococcus albus compared with the other supplements (P = 0.0120). There was also interaction between starch × oil for Selenomonas ruminantium (P = 0.0003), once low-starch supplement, with or without oil, decreased the number of Selenomonas ruminantium of Nellore steers. The addition of oil in the supplements decreased the number of Fibrobacter succinogenes (P < 0.0001), Ruminococcus flavefasciens (P < 0.0001), and Archeas (P < 0.0001), but increased of Anaerovibrio lipolytica (P < 0.0001), independently of starch level used. Oil supplementation decreases the intake, digestibility, acetate production, protozoa population, and fibrolytic rumen bacteria. The use of soybean hulls without oil supplementation may be effective to increase digestibility of CP, and Ruminococcus albus of finishing Nellore steers grazing Brachiaria brizantha cv. Xaraés during the dry season. The last study evaluated the fatty acid intake, fatty acid composition, and meat quality traits of 60 young Nellore bulls fed diets with two levels of starch-based supplement with or without a source of oil (ground soybean; GS). The supplements were corn without GS, corn associated with GS, soybean hulls (SH) without GS, and SH associated with GS. There were interaction between starch-based supplementation level and oil to intake of vaccenic (P < 0.01), linoleic (P < 0.01), Total PUFA (P = 0.01). Meat from animals supplemented with-high starch and without oil increased the percentage of vaccenic acid (P = 0.01). The use of low-starch supplements with oil increases intake of linoleic and total PUFA. Starch-based or oil supplementation not affect the myristic or palmitic acid content in the longissimus dorsi muscle. Oil supplementation increases the level of stearic acid and the n-6/n-3 ratio, but decreases the percentage of linolenic acid in muscle of Nellore bulls grazing Brachiaria brizantha cv. Xaraés during finishing phase.

No primeiro experimento, foram utilizados cento e quatro (PC inicial = 284 ± 38 kg) e sessenta (PC inicial = 424 ± 34 kg) tourinhos da raça Nelore com o objetivo de avaliar os efeitos de suplementos com alto ou baixo amido, associados ou não com uma fonte de óleo, sobre o desempenho e características finais da carcaça durante duas fases: recria e terminação, respectivamente. Os suplementos utilizados foram milho sem soja grão moída (SG), milho associado com SG, casca de soja (CS) sem SG, e CS associada com SG. Em relação ao desempenho dos animais durante a fase de recria, não houve interação (P = 0,14) entre o nível de amido e óleo para o PC final, GMD e ganho de carcaça. No entanto, a adição de óleo diminuiu o PC final (P = 0,01), GMD (P < 0,01), o ganho total (P < 0,01) e ganho de carcaça (P = 0,01). Por outro lado, durante a fase de terminação, não houve interação (P = 0,11) entre o nível de amido e óleo para PC final, GMD, PCQ, rendimento de carcaça, ganho de carcaça, espessura de gordura subcutânea e AOL. No entanto, os animais suplementados com óleo aumentaram o PC final (P = 0,01), GMD (P = 0,02), ganho total (P = 0,01), PCQ (P < 0,01), o ganho de carcaça (P = 0,01) e a espessura de gordura (P = 0,04). Além disso, houve efeito do tempo durante a fase de recria e terminação para os valores de GMD (P < 0,01) dos tourinhos da raça Nelore. A casca de soja tem um valor energético semelhante ao milho quando usado em suplementos para bovinos de corte em pastagem tropical durante a fase de recria e terminação. O uso de suplementação com óleo pode ser eficaz para melhorar o desempenho e as características finais da carcaça de tourinhos da raça Nelore em pastagens de Brachiaria brizantha cv. Xaraés, somente durante a fase de terminação. No outro experimento, objetivou-se avaliar os efeitos de suplementos com alto ou baixo amido, associados ou não com óleo, sobre o consumo, a digestibilidade, desempenho e emissões de metano (CH4) da fase de recria (n = 44, PC inicial = 250,69 ± 27 kg) e terminação (n = 44, PC inicial = 414 ± 12 kg) de tourinhos da raça Nelore alimentados com pasto tropical de Brachiaria brizantha cv. Xaraés durante a estação das águas e da seca, respectivamente. Oito animais foram abatidos em uma planta de frigorífico comercial de bovinos e serviu como grupo de referência no início de cada experimento. Os outros trinta e seis animais foram distribuídos em um delineamento experimental inteiramente casualizado (três animais por piquete e três piquetes por tratamento). O período experimental foi de 133 dias, divididos em um período de adaptação de 21 dias e quatro períodos de 28 dias cada. Os suplementos foram milho sem soja grão moída (SG), milho associado com SG, casca de soja (CS) sem SG, e CS associada com SG. Glicerina bruta foi utilizada em todos os suplementos para substituir (28% da MS) do milho ou da CS. Em relação à fase de recria, não houve interações entre nível de amido e suplementação com óleo sobre o consumo de MS (P = 0,67), FDN (P = 0,50) e EE (P = 0,47); sobre a digestibilidade da MS (P = 0,18) e do FDN (P = 0,42); sobre o PC final (P = 0,94), GMD (P = 0,40), e na EA (P = 0,37); e sobre as emissões de CH4 quando expressa em g/dia (P = 0,77), kg/ano (P = 0,77), g/kg CMS (P = 0,53). No entanto, independentemente do nível de amido utilizado, os animais suplementados com óleo aumentaram o consumo de EE (P < 0,01); diminuíram a digestibilidade MO (P = 0,04) e FDN (P = 0,03); e também, reduziram a emissão CH4 entérica quando corrigido para consumo de EB (P = 0,04) e EE (P < 0,01). Na fase de terminação, não houve interações entre nível de amido e suplementação com óleo sobre o consumo de MS (P = 0,90), FDN (P = 0,65) e EE (P = 0,56); sobre a digestibilidade da MS (P = 0,12) e FDN (P = 0,12); no PC final (P = 0,37), GMD (P = 0,41), EA (P = 0,47), PCQ (P = 0,83), rendimento de carcaça (P = 0,41), ganho de carcaça (P = 0,98), espessura de gordura (P = 0,36) e na AOL (P = 0,91); e sobre a emissão de CH4 quando expressa em g/dia (P = 0,78), kg/ano (P = 0,78), g/kg de CMS (P = 0,81), g/kg GMD (P = 0,48), e em g/kg de ganho de carcaça (P = 0,85). No entanto, independentemente do nível de amido utilizado, os animais suplementados com óleo diminuíram a digestibilidade da FDN (P = 0,03) e aumentaram a digestibilidade do EE (P < 0,01); aumentaram a espessura de gordura subcutânea (P = 0,01); e reduziram a emissão de CH4 entérico, expresso em g/dia (P = 0,04) e kg/ano (P = 0,04), e quando foi corrigido para consumo de EB (P = 0,02) e de EE (P < 0,01), e GMD (P = 0,02) para os animais suplementados com alto ou baixo amido. Em relação aos estudos de parâmetros ruminais, o objetivo foi avaliar o efeito da suplementação com óleo combinado com alto ou baixo amido sobre o consumo, a digestibilidade dos nutrientes, parâmetros de fermentação ruminal e o perfil dos microrganismos no rúmen, de novilhos da raça Nelore em pastagem de Brachiaria brizantha cv. Xaraés durante duas fases: recria e terminação. Na fase de recria, oito animais da raça Nelore, canulados no rúmen (424,8 kg ± 35,5) e com 20 meses de idade foram usados em um quadrado latino duplo 4 × 4, com um arranjo fatorial 2 × 2 dos tratamentos (alto ou baixo amido, com ou sem fonte de óleo) e um período experimental de 21 dias. Os suplementos foram milho sem soja grão moída (SG), milho associado com SG, casca de soja (CS) sem SG, e CS associada com SG. Os animais foram suplementados à taxa de 500 g/100 kg do peso corporal. Não houve interações entre nível de amido e suplementação com óleo sobre o consumo de MS e nutrientes (P > 0,01). A adição de óleo diminuiu o consumo de MS (P = 0,01), forragem (P < 0,01), MO (P = 0,01), PB (P = 0,02), FDN (P < 0,01) e EB (P = 0,01), independentemente do nível de amido utilizado. Animais alimentados com baixo amido e sem óleo apresentaram maior digestibilidade da MS (P < 0,01), MO (P < 0,01), PB (P < 0,01), FDN (P = 0,01) e EB (P = 0,01) do que os animais alimentados com outros suplementos. A adição de óleo nos suplementos diminuiu o pH (P = 0,02), NH3-N (P = 0,02), número de Dasytricha (P < 0,01), Isotricha (P < 0,01) e total de protozoários (P < 0,01). A percentagem de Ruminococcus albus (P = 0,0003), flavefaciens Ruminococcus (P = 0,0002), e Archeas (P < 0,0004) foram maiores para as dietas com baixo amido e sem óleo, do que para outras dietas. Além disso, os animais suplementados com óleo diminuiram o número de Fibrobacter succinogenes (P = 0,0003). Suplementação com óleo reduz o consumo, a população de protozoários e as bactérias fibrolíticas no rúmen. O uso de suplementos com baixo amido e sem óleo pode ser eficaz para aumentar a digestibilidade da MS e dos nutrientes, e também aumentar a população de Ruminococcus albus, Ruminococcus flavefaciens, e Archeas no rúmen de novilhos Nelore em pastejo, durante a fase de recria. Na fase de terminação, oito animais da raça Nelore, canulados no rúmen (514,5 kg ± 30,1) e com 24 meses de idade foram usados em um quadrado latino duplo 4 × 4, com um arranjo fatorial 2 × 2 dos tratamentos (alto ou baixo amido, com ou sem fonte de óleo) e um período experimental de 21 dias. Os suplementos foram milho sem soja grão moída (SG), milho associado com SG, casca de soja (CS) sem SG, e CS associada com SG. Os animais foram suplementados à taxa de 1000 g/100 kg de peso corporal. Não houve interações entre o nível de amido e óleo na suplementação em relação ao consumo de MS e nutrientes (P > 0,05). Animais suplementados com baixo amido e sem óleo apresentaram maior (10,77%) digestibilidade da PB (P = 0,01) do que aqueles suplementados com alto amido e sem óleo. A digestibilidade aparente total da MS (P < 0,01), MO (P < 0,01), FDN (P = 0,03) e EB (P = 0,02) diminuiu com uso do óelo na suplementação. Não houve interações entre amido × óleo para pH, N-NH3 e total de AGV (P > 0,05). Animais suplementados com óleo apresentaram uma menor produção de acetato (P < 0,01) do que aqueles suplementados sem óleo, independente do nível de amido. A adição de óleo nos suplementos diminuiu a população de Dasytricha (P < 0,01), Polyplastron (P < 0,21), e de Diploplastron (P = 0,04). Suplementando os animais com baixo amido e sem óleo, aumentou o número de Ruminococcus albus em comparação com os outros suplementos (P = 0,0120). Houve também uma interação entre amido × óleo para Selenomonas ruminantium (P = 0,0003), uma vez que, os suplementos com baixo amido, com ou sem óleo, diminuiram o número de Selenomonas ruminantium dos novilhos Nelore. A adição de óleo nos suplementos diminuiu o número de Fibrobacter succinogenes (P < 0,0001), Ruminococcus flavefasciens (P < 0.0001), e de Archeas (P < 0.0001), mas aumentou o de Anaerovibrio lipolytica (P < 0.0001). Suplementação com óleo reduziu o consumo, a digestibilidade, a produção de acetato, a população de protozoários e bactérias ruminais fibrolíticas. O uso da suplementação com casca de soja e sem óleo pode ser eficaz para aumentar a digestibilidade da PB, e a população de Ruminococcus albus de novilhos Nelore em pastagens de Brachiaria brizantha cv. Xaraés durante a fase de terminação. O último estudo avaliou a ingestão de ácidos graxos, composição de ácidos graxos e características de qualidade da carne de 60 tourinhos da raça Nelore alimentados com dietas com dois níveis de amido, com ou sem uma fonte de óleo (grão de soja moída; SG). Os suplementos foram milho sem soja grão (SG), milho associado com SG, casca de soja (CS) sem SG, e CS associada com SG. Houve interação entre o nível de amido e óleo sobre consumo de ácido vacénico (P < 0,01), linoleico (P < 0,01) e total PUFA (P = 0,01). A carne dos animais suplementados com alto amido e sem óleo aumentou a porcentagem de ácido vacênico (P = 0,01). O uso de suplementos com baixo amido e com óleo aumenta a ingestão de ácido linoléico e PUFA total. Suplementação à base de amido ou óleo não afeta o teor de ácido mirístico ou palmítico no músculo Longissimus dorsi. Suplementação com óleo aumenta o nível de ácido esteárico e a relação n-6/n-3, mas diminui a percentagem de ácido linolênico no músculo de tourinhos Nelore em pastagem de Brachiaria brizantha cv. Xaraés durante a fase de terminação.
Fontes de energia na suplementação de bovinos de corte em pastagens de Brachiaria brizantha cv. Xaraés
Keywords: Fatty acid; Glycerol; Methane; Nellore; Oil; Performance; Ácidos graxos; Desempenho; Glicerol; Metano; Nelore; Óleo